The Role of Social Contact in the Experience of Discrimination: Implications for Subjective Health Among Marriage Migrant Women in South Korea. Issue 1 (20th November 2015) - Cheon, Yuen Mi; Chung, Grace H.
Abstract : Several studies have found that various social contexts could serve a protective role for minorities facing discrimination. One of these contexts is frequency of social contact, which is known to be positively associated with health outcomes. The purpose of this study was to examine the frequency of social contact with various social groups as a protective factor against the negative association between perceived discrimination and subjective health. Using data from the 2009 Korean National Survey of Multicultural Families, a total of 27, 083 marriage migrant women were analyzed via hierarchical multiple regression. After controlling for socio‐demographic factors and Korean proficiency, the experience of discrimination was found to be significantly associated with lower levels of subjective health ( B = −0.22; P < 0.001). More frequent meetings with one's family of origin ( B = 0.02; P < 0.01) and in‐laws ( B = 0.06; P < 0.001) were associated with higher levels of subjective health, while more frequent meetings with neighbors were negatively associated ( B = −0.02; P < 0.001). More frequent contact with one's family of origin ( B = 0.03; P < 0.05), rather than with other groups, such as friends from their country of origin, in‐laws, and neighbors, seemed to reduce the negative influence of discrimination on subjective health.